The Role of Aspirin in the Prevention of Preeclampsia (A Mini Review) - Teguh Firdaus; Ilyas, Syafruddin (Talenta Publisher, 2025)
Preeclampsia is a severe pregnancy complication characterized by hypertension and proteinuria after 20 weeks of gestation. It is a leading cause of maternal and neonatal morbidity and mortality worldwide. Low-dose aspirin has been widely studied as a preventive measure for pre-eclampsia in high-risk women. This paper explores the role of aspirin in preventing preeclampsia, its mechanisms of action, and the effectiveness of different dosages and administration times. Studies have shown that aspirin, when taken before 16 weeks of gestation at a dosage of at least 100 mg per day, significantly reduces the risk of severe and early-onset preeclampsia. However, adherence to aspirin therapy remains a challenge, particularly among socioeconomically disadvantaged women. Increased education and healthcare access are crucial to optimizing the benefits of aspirin in preventing preeclampsia.